PROBLEMATIKA FUNDRAISING ZAKAT DI INDONESIA - Akhmad Zaeni; Danang Satrio (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2023)
This paper aims to identify and evaluate the problems that cause low zakat fundraising in Indonesia. This research uses a qualitative descriptive method by examining various literature as secondary data sources. The problem of zakat fundraising in Indonesia is caused by internal and external factors with the main internal factors being the quality of human resources, accessability, credibility and service. Meanwhile, the external factor is mainly due to the low literacy of zakat, the lack of zakat objects known to the public, the existence of unofficial zakat institutions and the low government support.